2007
DOI: 10.1021/ie0702678
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anions on the Photocatalytic Activity of Fe(III) Salts Impregnated TiO2

Abstract: This present work focuses on the photocatalytic activity of Fe(III) salt-impregnated TiO 2 catalysts for studying the effect of anion on the photocatalytic activity of the salt-impregnated catalysts. The salt-impregnated TiO 2 photocatalyst samples prepared using FeCl 3 , Fe(NO 3 ) 3 , and Fe 2 (SO 4 ) 3 were characterized by X-ray diffraction (XRD), UV-vis diffuse reflectance spectrophotometry (DRS), Fourier transform infrared absorption spectrophotometry (FT-IR), and surface area measurement by N 2 adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 40 publications
0
33
1
Order By: Relevance
“…The presence of cationic species (e.g., Mg 2+ , Li + , Na + and K + ) at the surface of TiO 2 stabilized I − at or near the surface, enhancing its rate of oxidation (by a photoionized dye) in DSSC applications [1463]. In other cases, adsorbed surface cations enhanced charge recombination [1464].…”
Section: Metal Cationsmentioning
confidence: 99%
“…The presence of cationic species (e.g., Mg 2+ , Li + , Na + and K + ) at the surface of TiO 2 stabilized I − at or near the surface, enhancing its rate of oxidation (by a photoionized dye) in DSSC applications [1463]. In other cases, adsorbed surface cations enhanced charge recombination [1464].…”
Section: Metal Cationsmentioning
confidence: 99%
“…For example, it is aqueous suspension of TiO 2 can greatly accelerate organic degradation under UV light [4][5][6]. Through a detailed study, Fe(OH) 2+ is found to be more active than other Fe(III) species for scavenging the conduction band electron of TiO 2 , whereas Fe(III) salt anions also have a great influence [7]. Unfortunately, after all Fe(III) species are transformed into Fe(II), the activity of Fe-containing TiO 2 became to be similar to blank TiO 2 , due to a very slow re-oxidation of Fe(II) back into Fe(III) by O 2 in an acidic medium.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of the oxidation and reduction of the pharmaceutical substance was caused mainly by a competitive adsorption of Cl , CO , HCO and SO anions in the active centers on the catalyst surfaces. In the case where different ions react with positively charged electron holes, the intensity of the generation of hydroxyl radicals, which are mainly responsible for the distribution of contaminants, is lowered [25]. This affects the inhibition of the reaction of oxidation and/or reduction of compounds.…”
Section: Influence Of Inorganic Anionsmentioning
confidence: 99%